Shelley - Waterlow, Sydney, 1878-1944 (Salt Lake City, UT : Project Gutenberg, 1998)
"Shelley" by Sydney Waterlow is a biographical account published in the early 20th century. The work delves into the life and times of the influential English Romantic poet Percy Bysshe Shelley, exploring not only his artistic endeavors but also the sociopolitical context surrounding him. Waterlow examines Shelley's complex personality, marked by both passionate idealism and significant emotional turmoil, shedding light on his enduring legacy within literature and political thought. At the start of the book, the author introduces Shelley within the tumultuous backdrop of early 19th-century England, highlighting the political oppression and societal unrest of the period. Waterlow discusses Shelley's early life, his expulsion from Oxford for his radical ideas, and his passionate pursuit of love and justice. The opening chapter provides an insightful analysis of Shelley's character traits, such as his intense emotional depth and sincere ideologies, while also foreshadowing the tragic elements of his life, including his tumultuous relationships and eventual demise. This initial exploration sets the tone for a deeper examination of both Shelley's literary works and the revolutionary fervor that shaped his artistic vision. (This is an automatically generated summary.)
Release date is 1998-06-01
Produced by An Anonymous Volunteer, and David Widger
Keywords: Shelley, Percy Bysshe, 1792-1822; Poets, English -- 19th century -- Biography